Genetic Polymorphism of Cancer Susceptibility Genes and HPV Infection in Cervical Carcinogenesis. (31st May 2011) - Nunobiki, Osamu; Ueda, Masatsugu; Toji, Eisaku; Yamamoto, Michiko; Akashi, Kyoko; Sato, Naomi; Izuma, Shinji; Torii, Kiyo; Tanaka, Ichiro; Okamoto, Yoshiaki; Noda, Sadamu
Abstract : It is widely accepted that specific human papillomavirus (HPV) types are the central etiologic agent of cervical carcinogenesis. However, a number of infected women do not develop invasive lesions, suggesting that other environmental and host factors may play decisive roles in the persistence of HPV infection and further malignant conversion of cervical epithelium. Although many previous reports have focused on HPV and environmental factors, the role of host susceptibility to cervical carcinogenesis is largely unknown. Here, we review the findings of genetic association studies in cervical carcinogenesis with special reference to polymorphisms of glutathione-S-transferase (GST) isoforms, p53 codon 72, murine double-minute 2 homolog (MDM2) gene promoter 309, and FAS gene promoter -670 together with HPV types including our recent research results.